DNA polymerase β suppresses somatic indels at CpG dinucleotides in developing cortical neurons - Noriyuki Sugo; Arikuni Uchimura; Risa Matsumoto; Hiro Nakayama; Shota Fujimoto; Saya Mizuno; Mayumi Higuchi; Masaaki Toshishige; Yasunari Satoh; Sayaka Wakayama; Teruhiko Wakayama; Takeshi Yagi (Proceedings of the National Academy of Sciences, 2025)
Somatic mutations in cortical neurons have been implicated in psychiatric disorders. While endogenous DNA damage and repair errors are potential contributors to these mutations during development, the underlying mutagenic mechanism remains unclear. Here, we investigated somatic mutations in immature cortical neurons using mouse somatic cell nuclear transfer-derived embryonic stem cells and whole-genome sequencing. Insertions and deletions (indels) were commonly observed in both repeat and nonrepeat sequences in wild-type cells. The loss of DNA polymerase β (Polβ), an enzyme involved in gap-filling during base excision repair and Ten-Eleven Translocation (TET)-mediated active DNA demethylation, in neural progenitor cells increased indel frequency by ~ninefold at cytosine-phosphate-guanine (CpG) dinucleotides and raised the frequency of structural variants by ~fivefold. These mutations were enriched in neuronal genes, leading to frameshift mutations, amino acid insertions/deletions, and the gain and loss of CpG sites in regulatory regions. Our findings suggest that Polβ preferentially repairs DNA lesions generated at CpG sites by TET-mediated active demethylation, thereby suppressing the mutagenesis that accompanies neuronal gene activation during cortical development.